Inexpressive law - Emanuela Carbonara; Francesco Parisi; Georg von Wangenheim (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
According to expressive law theories, expression of values is an important function played by the law. Expressive laws affect behavior, not by threatening sanctions or promising rewards, but by changing individual preferences and tastes and, in some cases, by affecting social norms and values. New laws, however, can run against sticky social norms, failing to achieve their expressive effects. By developing a dynamic model, in this paper we show that inexpressive laws (laws whose expressive function is undermined by sticky norms) can not only be ineffective but can push the values of society away from those expressed by the law. We study the effects of legal intervention on the values shared by members of society, considering the feedback effects between laws and social norms. Just like expressive laws can foster consensus in heterogeneous groups, inexpressive laws can create a social divide, even in previously homogeneous societies.
Keywords: K10; K42; D70; B52; Z13; 330; social norms; countervailing effect; expressive law; civil disobedience; Soziale Norm; Recht; Rechtsdurchsetzung; Dynamisches Modell; Theorie